Multi-instrumental Analysis of Tissues of Sunflower Plants Treated with Silver(I) Ions - Plants as Bioindicators of Environmental Pollution - Krizkova, Sona; Ryant, Pavel; Krystofova, Olga; Adam, Vojtech; Galiova, Michaela; Beklova, Miroslava; Babula, Petr; Kaiser, Jozef; Novotny, Karel; Novotny, Jan; Liska, Miroslav; Malina, Radomir; et al. (Sensors (Basel, Switzerland), 2008)
The aim of this work is to investigate sunflower plants response on stressinduced by silver(I) ions. The sunflower plants were exposed to silver(I) ions (0, 0.1, 0.5,and 1 mM) for 96 h. Primarily we aimed our attention to observation of basic physiologicalparameters. We found that the treated plants embodied growth depression, coloured changes and lack root hairs. Using of autofluorescence of anatomical structures, such aslignified cell walls, it was possible to determine the changes of important shoot and rootstructures, mainly vascular bungles and development of secondary thickening. Thedifferences in vascular bundles organisation, parenchymatic pith development in the rootcentre and the reduction of phloem part of vascular bundles were well observable.Moreover with increasing silver(I) ions concentration the vitality of rhizodermal cellsdeclined; rhizodermal cells early necrosed and were replaced by the cells of exodermis.Further we employed laser induced breakdown spectroscopy for determination of spatialdistribution of silver(I) ions in tissues of the treated plants. The Ag is accumulated mainlyin near-root part of the sample. Moreover basic biochemical indicators of environmentalstress were investigated. The total content of proteins expressively decreased withincreasing silver(I) ions dose and the time of the treatment. As we compare the resultsobtained by protein analysis - the total protein contents in shoot as well as root parts - wecan assume on the transport of the proteins from the roots to shoots. This phenomenon canbe related with the cascade of processes connecting with photosynthesis. The secondbiochemical parameter, which we investigated, was urease activity. If we compared theactivity in treated plants with control, we found out that presence of silver(I) ions markedlyenhanced the activity of urease at all applied doses of this toxic metal. Finally we studiedthe effect of silver(I) ions on activity of urease in in vitro conditions.
Keywords: Silver; Biochemical marker; Heavy metals; Plant biosensor; Sensors